Enhanced Methanization of Long-Chain Fatty Acid Wastewater at 20°C in the Novel Dynamic Sludge Chamber–Fixed Film Bioreactor - Singh, Suniti; Holohan, B. Conall; Mills, Simon; Castilla-Archilla, Juan; Kokko, Marika; Rintala, Jukka; Lens, Piet N. L.; Collins, Gavin; O’Flaherty, Vincent (Frontiers in Energy Research, 2020)
Lipid-containing wastewaters, such as those arising from dairy processing, are frequently discharged at temperatures ≤20°C. Their valorization at low ambient temperatures offers opportunities to expand the application of high-rate anaerobic wastewater treatment towards achieving energy neutrality by minimizing the energy demand for heating. Lipid hydrolysis generates long chain fatty acids (LCFA), which incur operational challenges and hinder stable bioreactor operation by inducing sludge flotation and washout, coupled with the added challenge of treatment at lower temperature (20°C). These challenges are tackled together uniquely during the treatment of LCFA-rich synthetic dairy wastewater (SDW) (33% COD-LCFA) through de-novo formed microbial granular sludge within the dynamic sludge chamber fixed film (DSC-FF) reactor. The novel reactor design facilitated sludge retention for the entire operational period of 150 days by containing settled, floating and LCFA-encapsulated granular sludge and biofilm within a single module. High COD removal efficiencies (87-98%) were achieved in the three replicated DSC-FF reactors, along with complete LCFA removal at 18-72 h HRT (LCFA loading rate of 220-890 mgCOD-LCFA/L·d) and partial LCFA removal at 12 h HRT (LCFA loading rate of 1333 mgCOD-LCFA/L·d). The high removal efficiencies of unsaturated and saturated LCFAs achieved are reported for the first time during continuous anaerobic wastewater treatment at low temperatures (20°C). Moreover, de novo granulation was achieved within 8 d from a combination of inoculum mixtures at a high LCFA concentration (33% COD-LCFA) in SDW. The results demonstrate the feasibility of the DSC-FF reactor for treating LCFA-rich wastewaters at discharge temperatures and offer potential for expanded and more energetically productive anaerobic valorization of lipid-rich wastewater.